2018
DOI: 10.1259/bjr.20170563
|View full text |Cite
|
Sign up to set email alerts
|

MRI guided stereotactic radiotherapy for locally advanced pancreatic cancer

Abstract: This trial was registered at www.clinicaltrials.gov (NCT01898741) on July 9, 2013.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 43 publications
0
43
0
Order By: Relevance
“…The concept of MR guidance on RT refers to various different issues, including the information added to the contouring of target volumes. Heerkens and colleagu es have described how multiparametric MR pretreatment scanning could improve the conventional Linac-based SBRT administration [ 86 ]. They defined target and OAR motion by the registration of four-dimensional (4D) CTscan simulations with both contrast-enhanced CT scan and MR (using a 1.5 Tesla scanner).…”
Section: Future Directionsmentioning
confidence: 99%
“…The concept of MR guidance on RT refers to various different issues, including the information added to the contouring of target volumes. Heerkens and colleagu es have described how multiparametric MR pretreatment scanning could improve the conventional Linac-based SBRT administration [ 86 ]. They defined target and OAR motion by the registration of four-dimensional (4D) CTscan simulations with both contrast-enhanced CT scan and MR (using a 1.5 Tesla scanner).…”
Section: Future Directionsmentioning
confidence: 99%
“…Given the ablative doses and the potential to injury, the translation in a clinical trial of the present strategy should be approached with a special attention to tumor and organ motion. Nowadays, MRI‐based image guidance has become a reality and the first experiences with MRI‐guided linear accelerators for the delivery of SBRT for pancreatic cancer have been recently reported 39 . This new technology not only offers a superior soft tissue imaging compared to cone beam CT but also allows the opportunity for adaptive replanning when significant interfraction variation is highlighted, 40 potentially increasing the safety and effectiveness of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, a need for new ways of visualizing and reporting dose and morphometric alterations will soon arise. Centers that lack MRL machines but are interested in MRIgRT for abdominal cancers may find the workflow outlined in Heerkens et al (72) informative. This phase I trial demonstrated a favorable toxicity profile (no treatment-attributable grade 3 acute or late toxicities) in 20 patients with unresectable pancreatic cancer who received 24 Gy/3 fx SBRT planned with multiparametric MRI sequences and sagittal cine MRI.…”
Section: Workflow Considerations For Integrated Mr Linear Acceleratorsmentioning
confidence: 99%